Between Reconciliation and Rights: The Judge Role in Child Advocacy in Algeria and Indonesia - Chami, Yassine; Benseghir, Mourad; Alshawabkeh, Mohammad Abdallah; Putri, Viorizza Suciani (Journal of Law and Legal Reform, 2025)
This research highlights the significant differences in how Algerian and Indonesian legal system approach reconciliation during the divorce process, particularly concerning the protection of children’s rights. Through an analysis of legal documents and relevant literature, this study evaluates the practical application of these legal provisions. The findings indicate that, although reconciliation efforts are required by law, failure to carry out such efforts does not impact the validity of the divorce decision. This underscores the notion that reconciliation should be pursued as a meaningful effort without altering the essence of divorce law. This research also highlights the need for a more integrated approach that combines legal security and child protection in the context of divorce.